Validation of an instrument for systematizing nursing care in pediatrics - Thalys Maynnard Costa Ferreira; Josefa Danielma Lopes Ferreira; Carla Lidiane Jácome dos Santos; Kenya de Lima Silva; Jacira dos Santos Oliveira; Glenda Agra; Marta Miriam Lopes Costa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to verify the validity of indicators' content referring to the instrument for data collection in children aged 0 to 5 years hospitalized in a pediatric clinic. Method: a cross-sectional methodological study was carried out with 11 experts between January and May 2018. For data collection, the steps for validating the instrument's content were respected. For data analysis, Content Validity Index and Kappa agreement analysis were used. Results: after content analysis, a Content Validity Index of 0.94 and Kappa 0.71 was issued according to the experts' suggestions 81.9%. Therefore, the instrument was suitable for applicability. Conclusion: the instrument proved to be valid in terms of content for pediatric care, contributing significantly to improving care for hospitalized children aged 0 to 5 years.